Arsenic fractionation and bioaccessibility in two alkaline Texas soils incubated with sodium arsenate - Datta, Rupali K.; Sarkar, Dibyendu; Makris, Konstantinos C. (My University, 2007)
Elevated arsenic (As) concentrations in urban soils with prolonged arsenical pesticide application history have increased the risk associated with accidental hand-to-mouth soil ingestion by children. Earlier work by the authors suggested that the conservative statement of 100% As bioaccessibility in soils was not valid for a set of acidic soils incubated with sodium arsenate. In this study, two alkaline Texas soils incubated with a commonly used As pesticide (sodium arsenate) were evaluated for their potential in reducing soil As bioaccessibility. The objective of this study was to evaluate the effects of incubation time and As load on soil As fractionation and bioaccessibility. Soils were subjected to a sequential As fractionation scheme, and bioaccessible As was quantified using an in vitro stomach phase test. Results showed a reduction in the water-soluble As fraction with incubation time (after 4 months), which remained unchanged after 12 months. This reduction with time was accompanied by an increase in the NaOH- and H2SO4-extractable As fractions, suggesting As sorption by amorphous Fe/Al hydroxides and/or Ca/Mg compounds, respectively. Organic/sulfides-bound As increased with incubation time after 12 months but not after 4 months of incubation. The aging effect was also observed with the amount of bioaccessible As at all As loads, showing significant positive correlations with the water-extractable and exchangeable As fractions. Bioaccessible As concentrations even after 12 months of incubation were not significantly reduced, suggesting that natural attenuation might prove inadequate to control As bioaccessibility in these alkaline soils.
Keywords: Arsenic; Bioaccessibility; Fractionation; In-vitro; Pesticide; Speciation